2002
DOI: 10.1098/rstb.2002.1114
|View full text |Cite
|
Sign up to set email alerts
|

The neural basis of the blood–oxygen–level–dependent functional magnetic resonance imaging signal

Abstract: Magnetic resonance imaging (MRI) has rapidly become an important tool in clinical medicine and biological research. Its functional variant (functional magnetic resonance imaging; fMRI) is currently the most widely used method for brain mapping and studying the neural basis of human cognition. While the method is widespread, there is insufficient knowledge of the physiological basis of the fMRI signal to interpret the data confidently with respect to neural activity. This paper reviews the basic principles of M… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

16
516
3
14

Year Published

2003
2003
2016
2016

Publication Types

Select...
6
4

Relationship

0
10

Authors

Journals

citations
Cited by 817 publications
(559 citation statements)
references
References 257 publications
16
516
3
14
Order By: Relevance
“…We acknowledge that the BOLD signal is an indirect measure of neural activity; previous work has shown that the BOLD signal correlates most highly with local field potentials, which can arise from either excitatory or inhibitory synaptic events (Logothetis & Wandell, 2004;Logothetis, 2002). A reduction in the observed signal can therefore arise in multiple ways, including (but not limited to) a decrease in inhibitory interneuron activity, a decrease in inter-regional recurrent activity, or a decrease in excitatory activity.…”
Section: Competition-mediated Ground Suppressionmentioning
confidence: 93%
“…We acknowledge that the BOLD signal is an indirect measure of neural activity; previous work has shown that the BOLD signal correlates most highly with local field potentials, which can arise from either excitatory or inhibitory synaptic events (Logothetis & Wandell, 2004;Logothetis, 2002). A reduction in the observed signal can therefore arise in multiple ways, including (but not limited to) a decrease in inhibitory interneuron activity, a decrease in inter-regional recurrent activity, or a decrease in excitatory activity.…”
Section: Competition-mediated Ground Suppressionmentioning
confidence: 93%
“…The BOLD signal is derived from changes in oxygenation within venous blood and is an indirect measure of neuronal activity; recent studies suggest that it is the increased metabolic activity at presynaptic terminals that drives the fMRI signal (Logothetis, 2002;Viswanathan and Freeman, 2007). The BOLD signal is dependent on blood flow, blood volume and blood oxygenation and is sensitive to non specific factors acting throughout the body such as fluctuations in PCO 2 and PO 2 , which means that the study of breath holding with fMRI is potentially problematic, even breath holds of a short duration (Kastrup et al, 1998;Liu et al, 2002).…”
Section: Methodological Issuesmentioning
confidence: 99%
“…In fact, there is no consensus on exactly which aspect of neural activity drives the hemodynamic response, and this is an active area of research. Experimental studies comparing electrophysiological measurements with BOLD and CBF changes have found that the hemodynamic responses correlate better with local mean field potential, rather then local spiking rates, suggesting that the hemodynamic response is dominantly driven by input synaptic activity rather than output spiking activity (Lauritzen, 2001;Lauritzen and Gold, 2003;Logothetis, 2002;Logothetis et al, 2001). Theoretical analyses of the energy budget for neuronal signaling provide some support for this picture as well (Attwell and Laughlin, 2001;Lennie, 2003).…”
Section: Neurovascular Couplingmentioning
confidence: 99%